2008
DOI: 10.1136/ard.2007.084707
|View full text |Cite
|
Sign up to set email alerts
|

Breast feeding, but not use of oral contraceptives, is associated with a reduced risk of rheumatoid arthritis

Abstract: In this study, long-term breast feeding, but not OC use, was associated with a significant reduction in the risk of RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
3
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(87 citation statements)
references
References 45 publications
2
79
3
3
Order By: Relevance
“…93,100,101 Changes in the female hormonal environment due to menstruation or Dovepress during pregnancy, while breast feeding, and/or through the use of oral contraceptive pills (OCP), appear to have a role in RA pathogenesis. 100,102 Increased breast feeding duration is protective for RA development, while the literature evaluating OCP use and parity is inconsistent, demonstrating protection in some studies and no associated risks in others. [101][102][103] The female systemic immune system is considered by some investigators to be more "reactive" than those of men.…”
Section: Linkagementioning
confidence: 99%
See 1 more Smart Citation
“…93,100,101 Changes in the female hormonal environment due to menstruation or Dovepress during pregnancy, while breast feeding, and/or through the use of oral contraceptive pills (OCP), appear to have a role in RA pathogenesis. 100,102 Increased breast feeding duration is protective for RA development, while the literature evaluating OCP use and parity is inconsistent, demonstrating protection in some studies and no associated risks in others. [101][102][103] The female systemic immune system is considered by some investigators to be more "reactive" than those of men.…”
Section: Linkagementioning
confidence: 99%
“…100,102 Increased breast feeding duration is protective for RA development, while the literature evaluating OCP use and parity is inconsistent, demonstrating protection in some studies and no associated risks in others. [101][102][103] The female systemic immune system is considered by some investigators to be more "reactive" than those of men. 100 This contention is supported by observations demonstrating higher immunoglobulin concentrations, enhanced cytokine production, greater resistance to infections, and stronger T cell responses in women, along with other characteristics not mentioned.…”
Section: Linkagementioning
confidence: 99%
“…Some studies suggested that the use of OCs is protective (18)(19)(20)(21). However, several studies have met no significance to demonstrate this association (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…[42][43][44][45][46] The majority of studies have found that past or current use of COCs has a protective effect against RA development. 47 In a recent case-control study, Berglin et al 48 reported a decreased risk for development of RA in women who had been using COCs for 7 years or more (OR: 0.37; 95% CI: 0.15-0.93). In the Norfolk Arthritis Register, which is a primary care-based cohort of patients with recentonset inflammatory polyarthritis, it was found that COC users have a better functional outcome than nonusers.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%